MELACAK DINAMIKA SIPIL-MILITER PASCA REVOLUSI MESIR - Atep A Rofiq (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2015)
Abstract: Tracking Civil-Military Dynamics after Egypt Revolution. Military revolution following Assisi’s administration shows that democratization process in Egypt and Middle East Countries has not been so easy. Military infiltration has taken in place since 60 years ago. Thus, causing the difficulty to decrease its influence in Egypt. The Movement of Civil supremacy lead by the Mass Organization so called “Ikhwanul Muslimin” and the others opposition has not yet succeeded. This situation proved that Arab Spring has failed and the democratization in Middle EastKey Words: Military leadership, Egyptian Revolution and Arab Spring Abstrak: Melacak Dinamika Sipil-Militer Pasca Revolusi Mesir. Revolusi Militer Kepemimpinan El-Sisi pasca Mesir memperkuat paradigma umum bahwa demokratisasi Mesir dan negara-negara Timur Tengah lainnya tidaklah mudah. Infiltrasi Militer terjadi sejak 60 tahun membuat kepemimpinan Mesir berakar dan sulit untuk menghapus dalam kepemimpinan Mesir. Supremasi sipil diperjuangkan Ikhwanul Muslimin dan pihak oposisi lainnya masih memerlukan waktu yang sangat lama dengan momentum politik berdarah. Situasi ini semakin menunjukkan bahwa Arab Spring telah gagal dan jalan demokratisasi di Timur Tengah mengalami kebuntuan.Kata kunci: Kepemimpinan Militer, Revolusi Mesir, Arab Spring DOI: 10.15408/sjsbs.v2i1.2244